Pemanfaatan Bahan Alam untuk Pemeliharaan Kesehatan di Desa Seleman Kecamatan Danau Kerinci - Rizky Yulion Putra; Anggraini, Gusnia; Ridha, M Sa'id; Fitri, Nadia; Nurfazila, Nurfazila; Rahmadina, Rahmadina; Kholilawati, Nelly; Sari, Wanti Puspita (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Health problems are still the main problems in Seleman Village, including diabetes, hyperlipidemia, gout, myalgia, and hypertension. This community service aims to improve the health and knowledge of residents in using medicine correctly and can utilize herbal plants as alternative treatments that can also be used as business opportunities. The methods used are counseling and demonstration as well as giving leaflets/brochures. This activity was carried out in the Seleman Village area. The target of counseling is the residents of Seleman Village with a total of 161 residents. From the pre-test results, 49.3% knew about hypertension, 40.42% knew about cholesterol, 56.78% knew about diabetes, and 51.87% knew about gout. After conducting educational activities about the disease, 95.34% knew about hypertension, 97.34% knew about cholesterol, 96.55% knew about diabetes, and 96.44% knew about gout. It can be concluded that from the community service carried out there is an increase in public knowledge on how to use medicine and independent use of herbal plants as alternative treatments derived from nature or known as